ANALISIS STRUKTUR, PERILAKU DAN KINERJA PEMASARAN PADA USAHA TANI KENTANG DI KECAMATAN KEJAJAR, KABUPATEN WONOSOBO - Ganjar Ndaru Ikhtiagung; Arif Nur Rahmadani; Berliana Ayu Dwika; Nancy Nurlita Sari; Nanda Puspita Zalfa Zahira; Nurmansyah Setyo Nugroho; Faidzin Firdhaus; Purwiyanto Purwiyanto (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Cilacap, 2022)
Kejajar District is the center of potato farming in Wonosobo Regency, where the area has a larger harvest area and higher potato production yield than other sub-districts. This study aims to determine the level of coordination and collaboration between marketing institutions so that potato products can be distributed optimally. If one chain is disturbed, it will affect the other chains. This research was conducted by purposive sampling, and the research location is the most productive potato area in Wonosobo. The study started in May and ended in June 2022. The number of respondents in the study was 52 people, consisting of 4 wholesalers, 3 middlemen/shippers, 15 retailers, and 30 farmers. The results showed that the four wholesalers had overall control over the sales of potatoes in the Kejajar District. This condition illustrates that the potato market at the farmer level tends to have a strongly oligopsony market structure. Wholesalers have considerable capital power, so they can control middlemen. The marketing margin shows that marketing channel one provides a high price share to farmers of 46.15%, and the farmer share analysis received by farmers as potato producers in Kejajar District can be said to be efficient because the selling price received by farmers is more than 40% of the price at the consumer level.